Advancing Knowledge and Skills through Mobile Learning in the Informal Economic Sector - Melanie Julie; Ugorji Iheanachor Ogbonnaya; Golekane Mthelebofu (Universitas Pendidikan Ganesha, 2025)
Workers in the informal economic sector often face limited access to formal education and professional training, which restricts their opportunities for knowledge and skills development. This study aims to explore how mobile learning supports the acquisition of knowledge and practical skills among informal economy workers in the Global South. The study employed a qualitative descriptive case study design. Data were collected through semi-structured interviews with 11 informal economy workers from Africa and Asia who had participated in mobile learning courses delivered via the Online Labour Academy (OLA) mobile application. The interview data were analyzed using thematic analysis to identify key patterns related to participants’ learning experiences and outcomes. The findings reveal that mobile learning has a transformative impact on informal workers. Participants reported increased competence, empowerment, digital literacy, problem-solving skills, and readiness to teach others. Mobile learning also enhanced their confidence to apply new knowledge in real work contexts and motivated them to continue learning independently. Furthermore, participants perceived that the skills acquired through mobile learning were demonstrable and marketable, contributing to improved employability and community-based knowledge sharing. This study concludes that mobile learning is an effective, inclusive, and scalable educational approach for supporting knowledge and skills development among informal economy workers. By providing flexible and accessible learning opportunities, mobile learning enables marginalized populations to overcome educational barriers, promotes lifelong learning, and contributes to socio-economic empowerment within the informal sector.